Phytochemical and Biological Effects of Newbouldia laevis : A Review - Rashed, Khaled (Plantae Scientia, 2021)
Newbouldia laevis (L) plant is a medium sized angiosperm and it is from Bignoniaceae family. In Nigeria vernacular, it is called Aduruku. It is popularly known as the tree of life or fertility tree in Nigeria. The plant has been found to be effective in the treatment of elephantiasis, dysentery, rheumatic swellings, syphilis, constipation, pile and as a vermifuge to round worms. It has also been found useful for earache, sore feet, chest pain, epilepsy and children's convulsion. Previous chemical studies proved that it has flavonoids, tannins, terpenes, phenolics, saponins, cardiac glycosides and alkaloids.